2016
DOI: 10.3390/ijerph13070728
|View full text |Cite
|
Sign up to set email alerts
|

Association by Spatial Interpolation between Ozone Levels and Lung Function of Residents at an Industrial Complex in South Korea

Abstract: Spatial interpolation is employed to improve exposure estimates and to assess adverse health effects associated with environmental risk factors. Since various studies have reported that high ozone (O3) concentrations can give rise to adverse effects on respiratory symptoms and lung function, we investigated the association between O3 levels and lung function using a variety of spatial interpolation techniques and evaluated how different methods for estimating exposure may influence health results for a cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
2
11
0
5
Order By: Relevance
“…sustained exhalation), and fewer studies reported short-term FVC effects for children (Fig 3). 7,8,11,14,15,19,21 However, generally consistent small decreases in FVC in children and adolescents were found, associated with short-term ozone exposures (-14 to -81 mL per 10 ppb ozone, -0.3% predicted, or a -11% difference).…”
Section: Short-term Ozone and Lung Function In Children And Adolescentsmentioning
confidence: 86%
See 1 more Smart Citation
“…sustained exhalation), and fewer studies reported short-term FVC effects for children (Fig 3). 7,8,11,14,15,19,21 However, generally consistent small decreases in FVC in children and adolescents were found, associated with short-term ozone exposures (-14 to -81 mL per 10 ppb ozone, -0.3% predicted, or a -11% difference).…”
Section: Short-term Ozone and Lung Function In Children And Adolescentsmentioning
confidence: 86%
“…A-C, Forest plots showing estimates of differences in FEV 1 associated with increases of 10 ppb ozone in adults, from studies published from 2013 through 2020 within the studies that reported differences in milliliters (A), within the studies that reported differences in percent predicted (B), and in studies that reported multiplicative changes (C), in percent differences. Two of the studies in younger adults found increased FVC associated with ozone exposure, 7,41 and a study that assessed indoor home ozone found an increase in FEV 1 to FVC ratio associated with ozone exposure. 43 Two studies that presented Results only graphically were left off the forest plots, 45,46 but both seemed to show nonsignificant decreases in FEV 1 and FVC associated with same-day ozone exposure.…”
Section: Q9mentioning
confidence: 99%
“…A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individual-level exposure assessments should be performed for some of the substances extracted in this study; this can be executed using biomarkers and diffusion or air pollution models [ 21 , 22 ]. Related methodologies should be developed for use in future surveys.…”
Section: Discussionmentioning
confidence: 99%